AN OVERVIEW OF US FDA WARNING LETTERS TO INDIAN PHARMACEUTICAL INDUSTRIES FOR cGMP VIOLATIONS PERTAINING TO STERILE PRODUCTS - Hanumant Gambhire; Monica Gulati; Sachin Kumar Singh; Atul Nasa; Neelu Goel (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Background: In the process to ensure the quality of pharmaceuticals, United States Food and Drug Administration (USFDA) notifies the manufacturers by the means of warning letters (WLs) in case of any significant violation of any of its regulations. For sterile products, careful compliance with Current Good Manufacturing Practices (cGMP) regulations needs to be done. Indian pharmaceuticals industries involved in the manufacturing of sterile products have been receiving a number of WLs from USFDA. This phenomenon has shown an upward trend in recent years. Increased number of warning letters to sterile product manufacturer is a matter of great concern due to the fact that any compromise in the quality of such products poses an exceptionally high risk to the patient, the product being generally administered directly into the human blood. It was, therefore, decided to analyze these letters and decipher the significant reasons for these WLs.Methods: Publically available USFDA letters (available under the law of the freedom of Information Act) sent to various Indian pharmaceutical companies were accessed from the USFDA website. Letters were manually screened and those related to sterile products violations of cGMP were selected based on their subject and content. The typical data collection tool (Excel Spreadsheet) with all letters of warning issued from January 2010 to May 2021 was used. Results: Overall, 105,402 warning letters for cGMP violations worldwide issued between January 2010 and May 2021 were reviewed. Out of these, Indian companies were found to have received 75 warning letters for the period from January 2010 to May 2021. Out of 75 warning letters issued to Indian pharmaceutical industries, 25 warning letters were found to be associated to sterile products, indicating that around 33% warning letters issued to Indian companies are associated with sterile products. Conclusion: Studied letters indicate that the USFDA is applying a systematic approach while assessing cGMP compliance and paying very close attention to aseptic practices. Another significant conclusion is that the Indian pharmaceutical industry needs to pay greater attention to maintenance of quality checks in the aseptic processing of products.